Health literacy of Sesotho-speaking patients diagnosed with chronic conditions in South Africa - Mita S. Mofoken; Marianne Reid; Melanie Pienaar; Mariette Nel (AOSIS, 2022)
Background: Health literacy influences patients' health outcomes, as their ability to read, interpret and apply health information associated with health-related decision-making. These decision-making skills need to be made up by patients diagnosed with chronic conditions - also Sesotho-speaking patients receiving treatment in public primary health care environments. Aim: The study aimed to assess the health literacy of Sesotho-speaking patients diagnosed with chronic conditions and to establish the associations between the sociodemographic data of patients and items of a health literacy test. Setting: This study was conducted in public healthcare (PHC) facilities in the Free State province, South Africa. Methodology: A quantitative descriptive cross-sectional design involved conveniently sampled patients with chronic conditions (n = 264) who were being treated at PHC facilities (n = 12) in the Setsoto subdistrict and who completed the Sesotho Health Literacy test during a structured interview. Descriptive statistics were calculated per group and compared by means of chi-square or Fisher's exact test and Kruskal-Wallis test. Results: Test results indicate high literacy levels in 35.6% (n = 94), moderate health literacy levels in 43.6% (n = 115) and low health literacy levels in 20.8% (n = 55) of participants. No association (p = 0.14) was found between health literacy level and gender or chronic conditions or between health literacy level and the participants' inability to read due to poor eyesight (p = 0.21). Positive associations (p ≤ 0.01) were established between a health literacy level and age and between health literacy level and education: participants with a South African School Grade Level 9-12 (p ≤ 0.01) had higher health literacy levels. Conclusion: Healthcare providers caring for Sesotho-speaking patients need to be sensitive about their patients' health literacy levels, as it may play a role in their health outcomes. Contribution: The value of the findings reported lies in the possibility of rapidly appraising the health literacy levels of a large indigenous population in South Africa diagnosed with chronic conditions.